PENERAPAN MODEL PEMBELAJARAN CONTEXTUAL TEACHING AND LEARNING TIPE LEARNING COMMUNITY UNTUK MENINGKATKAN PRESTASI BELAJAR SISWA PADA MATA PELAJARAN BAHASA INDONESIA TENTANG SURAT - EEN HENDARSIH (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2023)
This research is Classroom Action Research (PTK). Carried out collaboratively between researchers, observers and the subjects studied. The main aim of this research is to improve the learning achievement of Indonesian language regarding letters for class VII students. E MTsN 5 Brass. The subjects of this research were class VII students. E MTsN 5 Brass. This classroom action research process was carried out in two cycles, each cycle consisting of one meeting consisting of four actions, namely planning, implementation, action, observation and reflection. Learning activities in the first cycle obtained an average score of 68, while the second cycle obtained an average score of 85. This research concludes that through the contextual teaching and learning type learning community learning model, it can improve Indonesian language learning achievement regarding letters for class VII students. E MTsN 5 Brass. Apart from that, the contextual teaching and learning type learning community model can increase students' learning motivation in the learning process. ABSTRAKPenelitian ini merupakan Penelitian Tindakan Kelas (PTK). Dilaksanakan secara kolaboratif antara peneliti, observer, dan subyek yang diteliti. Tujuan utama dalam penetian ini adalah untuk meningkatkan prestasi belajar bahasa indonesia tentang surat siswa kelas VII. E MTsN 5 Kuningan. Subyek penelitian ini adalah siswa kelas VII. E MTsN 5 Kuningan. Proses penelitian tindakan kelas ini dilakukan dua siklus, setiap siklus satu kali peretemuan terdiri empat tindakan yaitu perencanaan, pelaksanaan, tindakan, observasi dan refleksi. Kegitan pembelajaran pada siklus pertama dengan memperoleh nilai rata-rata 68, sedangkan siklus kedua memperoleh nilai rata-rata 85. Penelitian ini berkesimpulan bahwa melalui model pembelajaran contextual teaching and learning type learning community dapat meningkatkan prestasi belajar bahasa indonesia tentang surat siswa kelas VII. E MTsN 5 Kuningan. Selain itu model pembelajaran contextual teaching and learning type learning community dapat meningkatkan motivasi belajar siswa dalam proses pembelajaran.